A 30-year trend of ischemic heart disease burden in a developing country; a systematic analysis of the global burden of disease study 2019 in Iran. (15th May 2023) - Koolaji, Sogol; Sharifnejad Tehrani, Yeganeh; Azadnajafabad, Sina; Saeedi Moghaddam, Sahar; Shahin, Sarvenaz; Ghamari, Azin; Ahmadi, Naser; Rezaei, Negar; Keykhaei, Mohammad; Tavolinejad, Hamed; Ghamari, Seyyed-Hadi; Abbasi-Kangevari, Mohsen; et al.
Abstract: Background: Evaluating the burden of ischemic heart disease (IHD) as the first cause of mortality worldwide is necessary to develop healthcare policies. This study aimed to report the national and subnational IHD burden and risk factors in Iran according to the Global Burden of Disease (GBD) study 2019. Methods: We extracted, processed, and presented the results of the GBD 2019 study regarding incidence, prevalence, deaths, years lived with disability (YLDs), years of life lost (YLLs), disability-adjusted life years (DALYs), and attributable burden to risk factors of IHD in Iran during 1990–2019. Results: Age-standardized death and DALY rates decreased by 42.7% (95% uncertainty interval, 38.1–47.9) and 47.7% (43.6–52.9) during 1990–2019, slower since 2011 and reached 163.6 deaths (149.0–176.2), 2842.7 DALYs (2657.0–3103.1) per 100, 000 persons in 2019. Meanwhile, with a lower reduction of 7.7% (6.0–9.5), the incidence rate reached 829.1 new cases (719.9–945.2) per 100, 000 persons in 2019. High systolic blood pressure and elevated low-density lipoprotein cholesterol (LDL-C) contributed to the highest deaths, and DALYs age-standardized rates in 1990 and 2019. They followed by high fasting plasma glucose (FPG), and high body-mass index (BMI) with an upward trend of contribution from 1990 to 2019. A convergence pattern in the provincial death age-standardized rate was observed, with the lowest rate in Iran's capital city; 84.7 deaths per 100, 000 (70.6–99.4) in 2019. Conclusion: The incidence rate reduced remarkably lower than the mortality rate, which necessitates promoting primary prevention strategies. Also, interventions should be adopted to control growing risk factors like high FPG, and high BMI. Highlights: 1990–2019: IHD mortality rate declined near 6 times more than the incidence rate in Iran. Mortality reduction slope had a considerable variation before and after 2011. Mortality to incidence ratio was higher in females. High fasting plasma glucose and high BMI are growing IHD risk factors.